Coaching is teamwork! The role of need-supportive coaching and the motivational climate in stimulating proactivity in volleyball teams - Van Puyenbroeck, S.; Stouten, J.; Vande Broek, G. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Team sports settings are challenging, dynamic environments in which coaches often benefit from proactive players who take initiative in providing valuable suggestions and feedback. Based on self-determination theory and achievement goal theory, the present study examined the mediating role of a mastery and performance motivational climate in the positive relation between coaches` psychological need-supportive behavior and team athletes` proactivity. The study sample consisted of 75 male and 105 female volleyball players (Mage = 21.92, SDage = 4.92), whose level ranged from the highest national level in Belgium to the regional levels. They completed a questionnaire assessing coach need support, motivational climate and three primary types of proactivity (voice, taking charge and upward communication). Multilevel structural equation modelling yielded a good fit for the hypothesized model. Consistent with our hypotheses, need support related positively to a mastery climate (ß = 0.74, p < .001), which, in turn, positively predicted proactivity (ß = 0.72, p < .001). Need-supportive coaching behavior negatively predicted a performance climate (ß = -0.39, p < .001). Rejecting our hypothesis, a performance climate positively predicted proactivity, albeit to a smaller extent than a mastery climate (ß = 0.21, p < .001). These findings suggest that a need-supportive coaching style enables coaches to create a mastery climate. Such a climate seems to encourage athletes to be proactive, which enables teams to effectively tackle encountered challenges. The weaker but significant positive relation between a performance climate and proactivity will be discussed within the framework of social interdependence theory.